Assessment of Wettability and Contact Angle of Bonding Agent with Enamel Surface Etched by Five Commercially Available Etchants: An In Vitro Study - Deepika Katyal; Aravind Kumar Subramanian; Adith Venugopal; Anand Marya (International Journal of Dentistry)
Background. The quantity and quality of the etching pattern produced by acids play a significant role in the wettability and contact angle of the adhesive with the enamel surface in orthodontics. The better the etch pattern, the more the surface energy of the enamel, better the penetration of the adhesive, which ultimately results in better bond strength. The present study aimed to evaluate the contact angle of the bonding agent with the enamel surface etched by five commercially available etchants and check if any difference existed between the five. Materials and Methods. Twenty-five human maxillary and mandibular central incisors and premolars extracted for orthodontic or dental purposes were used in this study as samples. The teeth were allocated into five groups based upon the etchant used to etch the enamel surface. After the samples were etched, a hard tissue microtome was used to create thin slices of the enamel surface. The samples were then exposed to bonding agent Ormco Enlight. The bonding agent was released in the form of droplets onto the enamel slices mounted on a contact angle goniometer. The contact angle values were tabulated, and statistical analysis using the one-way ANOVA test was carried out. Results. The contact angle measurements of the etchant group, DPI, were the lowest, while D-tech has the highest contact angle values. However, statistical analysis revealed no statistically significant difference between the contact angle measurements of the five groups included in the study. Conclusion. No statistically significant difference existed between the five etchant groups included in the study. However, commercially available etchant DPI showed lesser contact angle and thus better wettability in comparison to other groups. Further elemental analysis and surface analysis are required to validate these results.